2015
DOI: 10.1352/1944-7558-120.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions and Prader-Willi Syndrome: Global Deficit Linked With Intellectual Level and Syndrome-Specific Associations

Abstract: The aim of this study was to support the growing evidence suggesting that Prader-Willi Syndrome (PWS) might present with an impairment of executive functions (EFs) and to investigate whether this impairment is specific to patients with PWS or due to their intellectual disability (ID). Six tasks were administered to assess EFs (inhibition, switching, updating, cognitive estimation, and planning) to 17 patients with PWS and 17 age-matched healthy individuals. Performance was significantly impaired in the PWS gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 40 publications
3
24
0
1
Order By: Relevance
“…PWS patients display learning difficulties especially in observational learning 46 , 47 . A deficit in executive function has been observed with impaired mental switching 30 , 48 , and impaired inhibition capacities have also been noted 49 . Concerning visual perception, some authors have argued that patient with PWS display higher skills to detect similarities which possibly explain their high performance in puzzle processing 45 .…”
Section: Rdoc Approach and Pwsmentioning
confidence: 99%
“…PWS patients display learning difficulties especially in observational learning 46 , 47 . A deficit in executive function has been observed with impaired mental switching 30 , 48 , and impaired inhibition capacities have also been noted 49 . Concerning visual perception, some authors have argued that patient with PWS display higher skills to detect similarities which possibly explain their high performance in puzzle processing 45 .…”
Section: Rdoc Approach and Pwsmentioning
confidence: 99%
“…This difficulty with change of routine and inflexibility in PWS may be linked to a cognitive deficit in task switching [ 56 , 57 ]. Task switching requires being able to move from one task to a different task in a timely manner, an area of difficulty for individuals with PWS [ 56 , 86 ].…”
Section: Rigidity In Pwsmentioning
confidence: 99%
“…Based on the results of research that has been done, it is found that the predictive power of intellectual ability test scores on students' learning outcomes in the field of theory> students' learning outcomes in the field of practice.> This is because the learning of art in the field of theory is more the process of cognitive thinking [12] (knowledge), understanding of theories about art. This opinion is reinforced [2] by argument that, the term intellectual is defined as cognitive processes, thought processes, connecting power, ability to judge, and ability to consider.…”
Section: Resultsmentioning
confidence: 99%